The determinants of non-performing loan in four selected Asean countries / Muhammad Fadhil Abdul Rahman and Fatin Aqilah Mohd Jaafar - Abdul Rahman, Muhammad Fadhil; Mohd Jaafar, Fatin Aqilah (Faculty of Business and Management, 2019)
The purpose of this study is to determine the relationship between Non-performing loan with macroeconomics variable from 2008 to 2017 quarterly. Four selected Asean countries are Malaysia, Indonesia, Thailand and Vietnam. The Panel Regression of Fixed Effect Model is used as an empirical model in this study to investigate the relationship between Interest Rate (IR), Inflation Rate (IFR) and Unemployment Rate (UR) with Non-performing Loan. There are some tests involved in the study, which includes Descriptive Statistic, Unit Root Tests, Regression Analysis and Diagnostic Test. In unit root tests, the study used Levin, Lin, Chin (LLC) Test and Im, Pesaran, Shin (IPS) Test. Moreover, diagnostic tests consist of Normality Test, Multicollinearity Test and Autocorrelation Test. The results show that interest rate, inflation rate and unemployment rate are negative significant with Non-Performing Loan.